The relevance of financial inclusion on social problems, a causality demonstration - Vera Sánchez, Fernando (Pontificia Universidad Católica del Perú, 2023)
This study aims to contribute to the literature by assessing the causal relation among financial inclusion and social variables. Using Generalized Method of Moments and Directed Acyclic Graphs, on data for 92 countries for the year 2019, from the World Bank, we can prove that variables like number of automated teller machines and commercial bank branches (financial inclusion variables), have an impact on child mortality and education (social variables). This study´s limitations include the availability of data for every country, on this manner, we recommend a panel data analysis where we can incorporate time series analysis for the available data set, and other econometric techniques like Vector Autoregressive and Cointegration. To our knowledge, this is the first study to use the technique of Directed Acyclic Graphs to estimate causality in any research related with financial inclusion.
Keywords: Inclusión financiera; Mortalidad infantil; Método Generalizado de Momentos; Gráficas Dirigidas Acíclicas; https://purl.org/pe-repo/ocde/ford#5.02.04